EFFECT OF PHOSPHORUS AND ZINC FERTILIZATION ON BIOCHEMICAL COMPOSITION OF WHEAT - L. K. MISHRA, (The Bioscan, 2012)
Field trials were conducted to assess the response of conjunctive use of phosphorus and zinc fertilizer on the 1000-seed weight and certain biochemical components of three varieties of wheat (Triticum aestivum) viz: PBW- 343, HW-2425 and NW-1014. Results indicated that the phosphorus and zinc application had an synergistic impact on the 1000-seed weight and protein content of the wheat varieties. The increase in the doses of phosphorus and zinc had a positive impact on all the physical and biochemical characters of the wheat varieties. Application of phosphorus @ 60kg/ha and zinc @ 10kg/ha was found suitable to enhance the nutrient composition and certain bread making qualities of the wheat varieties